2005
DOI: 10.1002/micr.20127
|View full text |Cite
|
Sign up to set email alerts
|

Nerve repair by means of tubulization: Literature review and personal clinical experience comparing biological and synthetic conduits for sensory nerve repair

Abstract: Nerve repair is usually accomplished by direct suture when the two stumps can be approximated without tension. In the presence of a nerve defect, the placement of an autologous nerve graft is the current gold standard for nerve restoration. However, over the last 20 years, an increasing number of research articles reported on the use of non-nervous tubes (tubulization) for repairing nerve defects. The clinical employment of tubes (both biological and synthetic) as an alternative to autogenous nerve grafts is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
242
0
22

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 317 publications
(272 citation statements)
references
References 108 publications
(92 reference statements)
3
242
0
22
Order By: Relevance
“…26,27 Previous clinical experiences showed that successful results could be obtained in short-gap nerve repair with muscle-vein-combined conduits. 4,18 These results were recently confirmed by Marcoccio and Vigasio,19 who demonstrated the effectiveness of this technique in sec-ondary digital nerve reconstruction, highlighting the possibility of using the wound and surrounding tissues as donor sites for nerve repair in emergency surgery.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…26,27 Previous clinical experiences showed that successful results could be obtained in short-gap nerve repair with muscle-vein-combined conduits. 4,18 These results were recently confirmed by Marcoccio and Vigasio,19 who demonstrated the effectiveness of this technique in sec-ondary digital nerve reconstruction, highlighting the possibility of using the wound and surrounding tissues as donor sites for nerve repair in emergency surgery.…”
Section: Discussionmentioning
confidence: 59%
“…1,4 Experimen-tal research on rat demonstrated that filling the veins with fresh muscle fibers allow to obtain nerve regeneration that similar to that observed with nerve autografting. 22,23 Muscle fibers avoid conduit's collapse and promote axo-nal regeneration and Schwann cell migration by means of basal lamina scaffolds.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations